Extended X-ray study of M49: The frontier of the Virgo cluster - Su, Y.; Kraft, R. P.; Nulsen, P. E. J.; Jones, C.; Maccarone, T. J.; Mernier, F.; Lovisari, L.; Sheardown, A.; Randall, S. W.; Roediger, E.; Fish, T. M.; Forman, W. R.; et al. (Astronomical Journal, 2019)
The M49 group, residing outside the virial radius of the Virgo cluster, is falling onto the cluster from the south. We report results from deep XMM-Newton mosaic observations of M49. Its hot gas temperature is 0.8 keV at the group center and rises to 1.5 keV beyond the brightest group galaxy (BGG). The group gas extends to radii of 300 kpc to the north and south. The observations reveal a cold front 20 kpc north of the BGG center and an X-ray-bright stripped tail 70 kpc long and 10 kpc wide to the southwest of the BGG. We argue that the atmosphere of the infalling group was slowed by its encounter with the Virgo cluster gas, causing the BGG to move forward subsonically relative to the group gas. We measure declining temperature and metallicity gradients along the stripped tail. The tail gas can be traced back to the cooler and enriched gas uplifted from the BGG center by buoyant bubbles, implying that active galactic nucleus outbursts may have intensified the stripping process. We extrapolate to a virial radius of 740 kpc and derive a virial mass of 4.6 × 1013 M ⊙ for the M49 group. Its group atmosphere appears truncated and deficient when compared with isolated galaxy groups of similar temperatures. If M49 is on its first infall to Virgo, the infall region of a cluster could have profound impacts on galaxies and groups that are being accreted onto galaxy clusters. Alternatively, M49 may have already passed through Virgo once.
Keywords: Space and Planetary Science; Astronomy and Astrophysics